Thermally Activated Delayed Fluorescent Polymers: Structures, Properties, and Applications in OLED Devices. Issue 1 (21st September 2018) - Wei, Qiang; Ge, Ziyi; Voit, Brigitte
Abstract: Thermally activated delayed fluorescent (TADF) polymers are promising emitting materials to realize highly efficient, large‐scale, and low‐cost organic light‐emitting diodes (OLEDs) since they exhibit various advantages such as heavy‐metal‐free structures, 100% theoretical internal quantum efficiency, and ease of large‐area fabrication through solution process. At present, TADF polymers are still limited in category and complicated in preparation, which hinders their proceeding into industrial application. Besides, a still‐too‐low quantum efficiency poses a challenge for TADF‐polymer‐based OLEDs. In this review, different topologies and design strategies of the existing TADF polymers are covered, their structure–property relationships are illustrated, their first applications in OLED devices are discussed, and finally, an outlook of promising design rules for future TADF polymers is provided. The hope is to inspire researchers to develop TADF polymers prepared by easier synthesis strategies and higher external quantum efficiency to promote emitter application. Abstract : Thermally activated delayed fluorescent (TADF) polymers not only exhibit high excitons utilization efficiency but are also suited to prepare large‐scale and flexible organic light‐emitting diode (OLED) devices through cost‐efficient solution processing. Herein, the different design strategies of TADF polymers, their applications in OLED devices, and an outlook on the TADF polymers' future are provided.